Compétences linguistiques et culturelles des organisations de santé. Analyse critique de la littérature - Aucoin, Léonard (InfoVeille Santé, 2008)

Special report on French language health services planning in Ontario, 2009 - Boileau, François (Office of the French Language Services Commissioner, 2009)

Barrières linguistiques dans l'accès aux soins de santé - Bowen, Sarah (Santé Canada, 2001)

Language barriers in access to health care - Bowen, Sarah (Health Canada, 2001)

La formation des professionnels de la santé au Nouveau-Brunswick ou l'application du principe de I'inégalité - Braën, André (Administration publique du Canada, 2008)
Sommaire: Comme partout ailleurs au Canada, le régime des soins médicaux et hospitaliers du Nouveau-Brunswick est universel. Les services de santé qui sont ainsi offerts à la population sont fournis sur une base individuelle, sans égard à la race ou à la langue de l'individu. D'autre part, le Nouveau-Brunswick est la seule province canadienne qui a proclamé officiellement l'egalité juridique des deux communautés linguistiques qui la composent. Dans un tel contexte, l'assurance de la disponibilité de services de santé dans sa propre langue devient un principe général important; elle affecte directement la qualité des services fournis à la minorité francophone de cette province ainsi que le développement de ses institutions hospitalières. L'auteur cherche ici a analyser si, au-delà de cette dialectique juridique dont semble friand le Nouveau-Brunswick, l'égalité de fait est recherchée dans le secteur de la formation des spécialistes de la santé. Puisque cette formation est extrêmement onéreuse et étant donné le nombre restreint de ses habitants, le Nouveau-Brunswick a conclu plusieurs accords avec des provinces voisines dans le but de permettre à ses étudiants de s'inscrire dans des programmes de sciences de la santé non disponibles dans la province. Ayant choisi l'angle linguistique, l'auteur examine les structures mises en place pour appliquer ces accords, le nombre et la qualité linguistique des étudiants ainsi que les sommes dépensées par le Nouveau-Brunswick dans le cadre de l'application de ces ententes. Finalement, il mesure l'intensité de l'effort que fournit cette province pour former des spécialistes francophones.

Évaluation de la validité des preuves présentées dans l’étude intitulée "Language Barriers in Health Care Settings: An Annotated Bibliography of the Research Literature" - Bureau d'appui aux communautés de langue officielle (Santé Canda, 2008)

Les minorités prennent la parole : résultats de l'Enquête sur la vitalité des minorités de langue officielle - Corbeil, Jean-Pierre; Grenier, Claude; Lafrenière, Sylvie (Statistique Canada, 2007)

Minorities speak up: Results of the survey on the vitality ot the Official-Language Minorities - Corbeil, Jean-Pierre; Grenier, Claude; Lafrenière, Sylvie (Statistics Canada, 2007)

Préparer le terrain pour la santé en français. Rapport final - Duguay, Lise; Fortin, Pierrette; Hendriks, Edouard; Losier, Barbara; Pinet, Léo-Paul; Schofield, Aurel; St-Pierre-Ellis, Lyne; Thébeau, Marcel; Thériault, Bernadette; Vienneau, Gilles (La Société Santé et Mieux-être en français du Nouveau-Brunswick, 2007)

Les données administratives et d’enquêtes sur l’état de santé et l’accès aux services des communautés francophones en situation minoritaire : potentiel d’analyse et état de situation. Rapport - Gaboury, Isabelle; Guignard Noël, Josée; Forgues, Éric; Bouchard, Louise (Consortium national de formation en santé, 2009)

Les discours sur la santé des organismes franco-ontariens : du rapport Dubois à la cause Montfort - Gilbert, Anne; Kérisit, Michèlle; Dallaire, Christine; Coderre, Cécile; Harvey, Jean (Reflets, 2005)

Language as a barrier to care for Xhosa-speaking patients at a South African paediatric teaching hospital - Levin, M. E. (South African Medical Journal = Suid-Afrikaanse Tydskrif Vir Geneeskunde, 2006)
BACKGROUND: Disease is closely linked to the social context in which we live. Difficulty with communication, cultural incompatibility between patients and health care providers and socioeconomic obstacles are important barriers to quality care when doctors and patients come from different backgrounds and speak different languages. Red Cross War Memorial Children's Hospital (RCH) is a paediatric teaching hospital in Cape Town where staff members communicate mainly in English or Afrikaans, while many patients speak Xhosa as their first language. OBJECTIVES: The study aimed to identify barriers to optimal care for Xhosa-speaking parents of patients at RCH. The contribution of language difficulties was assessed as a possible barrier to health care for this group. DESIGN: A questionnaire was developed and administered to 53 Xhosa-speaking parents of children admitted to the short-stay ward at RCH. The questionnaire examined parents' perceptions of barriers to their children's care, using openended questions, closed-ended questions and selection from lists. RESULTS: Parents experienced significant structural and socioeconomic barriers to access of health care for their children. Language and cultural barriers were cited by more parents as a major barrier to health care than structural and socioeconomic barriers. Parents did not have access to same-language practitioners, as only 6% of medical interviews were conducted partly or wholly in the patient's home language. Of the 94% of interviews where no Xhosa was spoken by medical staff, 21% were conducted with the aid of an interpreter (formal or ad hoc) and in 79% no interpreter was used. Parents experienced difficulties with understanding the doctors (64%), making themselves understood (54%) and asking questions (38%). Sixty-nine per cent of parents were dissatisfied with communication between themselves and their doctors and 45% were concerned about negative effects of poor communication on them or their children. Parents tended to blame their own linguistic limitation rather than those of the doctors.
Keywords: Adolescent; Adult; Communication Barriers; Cultural Characteristics; Health Care Surveys; Health Services Accessibility; Hospitals, Pediatric; Hospitals, Teaching; Humans; Language; Middle Aged; Multilingualism; South Africa

Les répercussions des problèmes de communication sur la prestation de soins de santé de qualité aux communautés et patients de langue minoritaire - MacLean, Patsy; Robinson, Constance; Lewis, Kay; HRA, firme d’experts-conseils (Réseau des services de santé en français de l’Île-du-Prince-Édouard et Société Santé en français, 2007)

Misinterpretation: Language proficiency, recent immigrants, and global health disparities - Pottie, Kevin (Canadian Family Physician, 2007)

Préparer le terrain. Soins de santé primaires en français dans le Sud de l'Ontario. Rapport régional - Réseau franco-santé du Sud de l'Ontario (2006)

The effects of a language barrier in a South African district hospital - Schlemmer, A.; Mash, B. (South African Medical Journal = Suid-Afrikaanse Tydskrif Vir Geneeskunde, 2006)
BACKGROUND: Communication between health workers and patients at Hottentots Holland Hospital (HHH) is hindered by staff and patients not speaking the same language. HHH is a district hospital in the Cape Town Metropolitan District of the Western Cape where staff mainly speak Afrikaans or English and a large number of patients mainly Xhosa. OBJECTIVES: The study aimed to explore the effects of this language barrier on health workers and patients at HHH. DESIGN: Three focus group interviews were held with 21 members of staff and 5 in-depth patient interviews were conducted. RESULTS: The language barrier was found to interfere with working efficiently, create uncertainty about the accuracy of interpretation, be enhanced by a lack of education or training, cause significant ethical dilemmas, negatively influence the attitudes of patients and staff towards each other, decrease the quality of and satisfaction with care, and cause cross-cultural misunderstandings. CONCLUSION: The effects of the language barrier were considerable and persistent despite an official language policy in the province. The training and employment of professional interpreters as well as teaching of basic Xhosa to staff are recommended.
Keywords: Communication Barriers; Health Services Accessibility; Hospitals, District; Humans; Language; Multilingualism; Outcome Assessment, Health Care; Professional-Patient Relations; South Africa; Surveys and Questionnaires